Potential Therapeutic Role of N-acetylcysteine Against Risperidone-Induced Oxidative Stress in Caenorhabditis elegans : Protective Role of NAC in Risperidone Toxicity - Dhanik, Babita; Rakhi Agarwal, Rakhi Agarwal (Iranian Journal of Pharmaceutical Sciences, 2026)
Risperidone, an antipsychotic drug, is widely used for treating mental health disorders such as schizophrenia, psychosis, etc. Despite its therapeutic benefits, Risperidone has been linked to oxidative stress through several pathways, including increased lipid peroxidation, mitochondrial and lysosomal dysfunction, excessive production of reactive oxygen species (ROS), and depletion of intracellular antioxidants such as glutathione (GSH). These changes impair membrane integrity, disrupt cellular redox balance, and increase the cytotoxic consequences. To address this, the current study examined how N-acetylcysteine (NAC), a potent thiol antioxidant and glutathione precursor, protects against oxidative damage induced by Risperidone. We assessed oxidative stress indicators such as ROS, lipid peroxidation (MDA), antioxidant enzyme activities (GSH, SOD, CAT), and oxidative stress tolerance (tBHP assay) using Caenorhabditis elegans as a model organism. Results showed decreased worm survival, increased oxidative stress markers, and compromised antioxidant defences with 50 μM risperidone exposure. However, pretreatment with 10 mM NAC effectively reduced ROS levels, enhanced GSH, and reduced lipid peroxidation, thereby improving survival under oxidative stress conditions (tBHP assay), which supports its role in maintaining redox balance. These findings suggest that risperidone-induced toxicity is mediated through oxidative stress, and NAC may offer a protective effect, presenting a potential therapeutic approach to mitigate its damaging effects.